HUBUNGAN ANTARA BODY IMAGE DENGAN SELF ESTEEM PADA PENYANDANG DISABILITAS FISIK DI SENTRA TERPADU PROF. DR. SOEHARSO DI SURAKARTA: HUBUNGAN ANTARA BODY IMAGE DENGAN SELF ESTEEM PADA PENYANDANG DISABILITAS FISIK DI SENTRA TERPADU PROF. DR. SOEHARSO DI SURAKARTA - Nur Rachmah, Intan; Hartanto, Agit Purwo (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
Having physical deficiencies, most of the time,affect the psychology of individuals, especially people with physical impairments. The role of family, community, playmates, and others contribute to the stages of psychological development of individuals with physical impairments. This also has a significant impact on their body image and self-esteem. People with physical disabilities often face stigmatization, discrimination and unfavorable treatment from society because of their physical differences. According to the some studiesbody image has a great influence on people with physical impairments due totheir physical limitations. Johs and Wardle (2005) (in Stojcic et al., 2020) further discussed that dissatisfaction with body image is associated with depression, stress and low self-esteem. Therefore, the author wants to know The Relationship between Body Image and Self Esteem for People with Physical Disabilities at the Prof. Dr. Soeharso Integrated Center, Surakarta. This research approach uses quantitative correlational. The subjects in this research covers 30 respondents. Meanwhile, the sampling technique uses a total technique. Data collection uses a questionnaire or instrument supporting Body Image and Self-Esteem with a Likert scale measuring instrument that has been modified by eliminating neutral answers. Hypothesis testing in this research uses Product Moment correlation analysis with the help of the Statistical Package for Social Sciences (SPSS) program version 23. Based on the Product Moment correlation from Pearson, an rxy was obtained of 0.052 with a significant (2-tailed) p value of 0.00 (p<0.01), indicating that there is a positive relationship between social support and mental career readiness; the rxy value shows a positive direction. This means that the correlation coefficient can be tested by consulting the calculated r with the r product moment table for a significance level of 5% with N= 30 of 0.361. Because r count = 0.052 > r table = 0.361. The results of the correlation coefficient of 0.052 are consulted in the strong category, this is based on the interpretation of the correlation figures.